2002
DOI: 10.1080/02656730110103519
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of experimental rabbit liver tumours by selectively targeted hyperthermia

Abstract: Experimental rabbit liver tumours were preferentially heated to therapeutic temperatures without compromising the surrounding normal hepatic parenchyma. This was achieved by the use of hepatic arterially infused ferromagnetic microspheres that heat as a result of magnetic hysteresis loss when exposed to an alternating magnetic field. Treatment sessions involving a single 20-min exposure to the alternating field resulted in total suppression of tumour growth at 14 days compared to controls, in which tumour size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 12 publications
(7 reference statements)
0
20
0
Order By: Relevance
“…In another recent study by Jones et al [23], good local tumor control was achieved using the same microspheres and tumor model as used in our study. The finding that not all of the tumor tissue was necrotic in both this study and that by Jones and colleagues suggests that AEH treatment could be improved by longer treatment times and or repeated treatments, together with the addition of different treatment modalities such as radiotherapy and chemotherapy.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In another recent study by Jones et al [23], good local tumor control was achieved using the same microspheres and tumor model as used in our study. The finding that not all of the tumor tissue was necrotic in both this study and that by Jones and colleagues suggests that AEH treatment could be improved by longer treatment times and or repeated treatments, together with the addition of different treatment modalities such as radiotherapy and chemotherapy.…”
Section: Discussionmentioning
confidence: 76%
“…This same principle can be used to target liver tumors with ferromagnetic particles, and therefore high temperatures, on exposure to an alternating magnetic field. It has been reported that it is possible to effectively target liver tumors in small animal models with hyperthermia using this technique [20][21][22][23]; two of these recent studies have reported significant tumor response [21,23].…”
mentioning
confidence: 99%
“…Jones et al [27] achieved positive temperature differences between tumor and normal liver and subsequent therapeutic responses in experimental rabbit liver tumors after arterially infused ferromagnetic microspheres. Although encouraging results have been achieved in the above-mentioned preclinical studies on arterial embolization hyperthermia, only Granov and co-workers reported on clinical use [28].…”
Section: Introductionmentioning
confidence: 99%
“…These results demonstrate that the antitumor effectiveness of magnetohyperthermia treatment can be associated with cell death in the target tissue and is consistent with the tumor regression observed in hamsters treated with this magnetic fluid composition and AMF. The treatment of tumors via magnetic heating has already demonstrated promising results in other tumors [16,[46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%